Impact on Medical Education and the Medical Student’s Attitude, Practice, Mental Health, After One Year of the Covid-19 Pandemic in Indonesia - Turana, Yuda; Primatanti, Putu Asih; Sukarya, Wawang S.; Wiyanto, Marwito; Duarsa, Artha Budi Susila; Wratsangka, Raditya; Adriani, Donna; Sasmita, Poppy Kristina; Budiyanti, Ecie; Anditiarina, Dasti; Ainin, Dina Qurratu; Sari, Kartika; et al. (Frontiers in Education, 2022)
The COVID-19 pandemic has caused disruptions in educational institutions across the country, prompting medical schools to adopt online learning systems. This study aims to determine impact on medical education and the medical student’s attitude, practice, mental health after one year of the Covid 19 pandemic in Indonesia. This study utilized a cross-sectional design. An online questionnaire was distributed digitally to 49 medical schools that belong to The Association of Indonesian Private Medical Faculty in Indonesia from February - May 2021. A total of 7949 medical students participated in this study. Sampling was carried out based on a purposive technique whose inclusion criteria were active college students. Instruments included demographic database, medical education status, experience with medical tele-education, ownership types of electronic devices, availability of technologies, programs of education methods, career plans, attitudes towards pandemic, and the mental health of respondents. Univariate and bivariate statistical analysis was conducted to determine the association of variables. All statistical analyses using (IBM) SPSS version 22.0. Most of the respondents were female (69.4%), the mean age was 20.9 ± 2.1 years. More than half of the respondents (58.7%) reported that they have adequate skills in using digital devices. Most of them (74%) agreed that e-learning can be implemented in Indonesia. Nevertheless, only 56.9% agreed that e-learning can be used as an aspect of clinical education. The infrastructure aspects that require attention are Internet access and the type of supporting devices. Approximately 28.1% stated that they had economic problems, only 2.1% delayed their education due to economic problems. Nearly 40% of respondents expressed anxiety symptoms. The infrastructure and competency of its users are required for E-learning to be successful. However, access to the internet remains a problem. On the other side, the pandemic has disrupted mental health, with fears of being infected with SARS-CoV-2, the loss of opportunities to apply for specialty training, and the potential for increased financial difficulties among medical students. Our findings can be used to assess the current educational process in medical schools and maximize e-learning as an alternative means of preparing doctors for the future.